Hemicyanine-based colorimetric and near-infrared fluorescent off-on probe for Hg2+ detection and imaging in living cells and zebrafish. (December 2020) - Yuan, Gang; Lv, Hehong; Liu, Heng; He, Hanping; Sun, Qi; Zhang, Xiuhua; wang, Shengfu
Abstract: Herein, a novel near-infrared fluorescent probe (Cy-PT) for the detection of Hg 2+ was designed and synthesized, which contained a hemicyanine skeleton as the near-infrared (NIR) fluorophore and carbonothioate moiety as the recognition unit. The very weak fluorescence of Cy-PT is greatly enhanced due to the destruction of thiocarbonate moiety by Hg 2+, generating a hydroxyl group. The study shows that Cy-PT exhibits many advantages including NIR emission (708 nm), colorimetric change, off-on fluorescence, remarkably large Stokes shift (120 nm), rapid response, excellent sensitivity and high selectivity. In addition, Cy-PT can be used as a direct visualization detector for Hg2+ detection, allowing further application using test paper. Subsequent fluorescence imaging shows that Cy-PT probe has high ability to enter living cells and bodies, generating strong NIR fluorescence response in the presence of Hg 2+ . This study indicates that Cy-PT probe is a good candidate for Hg 2+ detection in colorimetric and near-infrared fluorescence, which can be developed into an efficient method for Hg 2+ detection in complex living samples. Graphical abstract: Image 1 Highlights: A novel probe (Cy-PT) for detecting Hg 2+ was designed and synthesized. Cy-PT exhibits many advantages including NIR emission (708 nm), colorimetric change, off-on fluorescence, remarkably large Stokes shift (120 nm), rapid response, excellent sensitivity and high selectivity. Cy-PT probe has high ability to enter living cells and bodies, generating strong NIR fluorescence response in the presence of Hg 2+ .